Evaluation Study of Green Open Space in Pulogadung Industrial Area Based on Ministry of Industry Standards Towards Green-Blue Open Space - Monalisa Monalisa; Agus Suroso; Sutrisno Sutrisno (Reka Buana : Jurnal Ilmiah Teknik Sipil dan Teknik Kimia, 2022)
One of the harmful effects of limited green space is high air pollution. As many as 7.78% of residents who live in East Jakarta suffer from ISPA. This problem can be overcome by building green open spaces around settlements. This study aims to analyze and evaluate green open spaces located in the Pulogadung Industrial according to the Minister of Industry's regulation towards the green-blue open space concept. The method used in this research is descriptive quantitative. The results of this study are that the Pulogadung industrial area has land that functions as a green open space of 30.49 hectares, or around 6% of the entire area. Based on the Minister of Industry regulation, a minimum green open space is 10% of the total area. It proves that green open space in the Pulogadung industrial area must meet the assessment criteria. The Pulogadung industrial area has green-blue open space. However, it does not fulfill the green-blue open space concept according to the ATR/BPN ministerial regulations in terms of fulfilling socio-cultural and aesthetic functions because it does not provide recreational facilities, and tree planting does not show a symmetrical pattern. ABSTRAKSalah satu dampak buruk dari RTH yang terbatas adalah polusi udara yang tinggi. Sebanyak 7,78% warga yang bertempat tinggal di Jakarta Timur menderita penyakit ISPA. Masalah tersebut dapat diatasi dengan cara membangun ruang terbuka hijau di sekitar permukiman. Tujuan penelitian ini adalah menganalisa dan mengevaluasi ruang terbuka hijau yang berlokasi di Kawasan Industri Pulogadung berdasarkan peraturan menteri perindustrian menuju konsep green-blue open space. Metode yang digunakan dalam penelitian ini adalah deskriptif kuantitatif. Hasil pembahasannya adalah Kawasan industri pulogadung memiliki lahan yang difungsikan sebagai ruang terbuka hijau sebesar 30,49 Ha atau sekitar 6% dari total luas areal. Berdasarkan peraturan menteri perindustrian, minimal luas RTH yaitu 10% dari keseluruhan luas kawasan. Hal ini menunjukkan bahwa RTH yang berlokasi di kawasan industri pulogadung belum memenuhi kriteria penilaian. Kawasan industri pulogadung memiliki ruang terbuka hijau-biru namun belum memenuhi konsep green-blue open space sesuai peraturan menteri ATR/BPN dalam hal pemenuhan fungsi sosial budaya dan fungsi estetika karena tidak menyediakan fasilitas rekreasi dan penanaman pohon tidak menunjukkan pola simetris.